Case report: Corticosteroid-resistant acute fibrinous and organizing pneumonia with myelodysplastic syndrome - Jiang, Dingyuan; Chen, Xueying; Li, Jun; Zhao, Ling; Dai, Huaping (Frontiers in Medicine, 2023)
Acute fibrinous and organizing pneumonia (AFOP) is a lung disease with an unusual pathological pattern. The definitive diagnosis of AFOP relies on pathological evidence of intra-alveolar fibrin exudate, lymphoplasmacytic infiltrate, and the absence of a hyaline membrane. Furthermore, its etiology is difficult to confirm, and corticosteroids are usually effective. Herein, we report the case of a young male who presented with high fever, hemocytopenia, and consolidation in both lungs. The initial misdiagnosis was community-acquired pneumonia. Subsequently, a lung biopsy revealed abundant fibrin and fibroblast exudates in the alveolar spaces, indicating AFOP. In addition, bone marrow biopsy and karyotype analysis demonstrated that the patient simultaneously had myelodysplastic syndrome (MDS) and hemophagocytic lymphohistiocytosis. In this case, the AFOP was considered secondary to MDS; however, the disease did not respond to glucocorticoid treatment or chemotherapy. Hence, AFOP should be considered in patients with underlying hematological diseases, and early identification and diagnosis are important. Furthermore, the management of patients with severe AFOP requires further investigation.